Peran Satisfaction Dalam Memediasi Pengaruh Service Quality Dan Customer Trust Terhadap Customer Loyalty Nasabah Agen BRIlink - Pramesti, Niken Ayu; Tiarawati, Monika (Jurnal Ilmiah Wahana Pendidikan, 2023)
PT. Bank Rakyat Indonesia (Persero) Tbk has been appointed as the government's strategic partner and has a special role to reach people who have not been touched by banking access. However, inversely, BRILink agents are state-owned banking agents who have had many cases of fraud. This study aims to determine the effect of service quality and customer trust on customer loyalty through satisfaction as a mediating variable for BRILink Agent customers. This research is a type of descriptive research that is analyzed quantitatively and uses a non-probability sampling technique with the path analysis method. Respondents in this study were BRILink agent customers aged at least 17 years who had a BRI savings account and had made financial transactions at a BRILink agent at least 2 times in the last 6 months. The sample used was 220 respondents online using judgmental sampling. The results of the study show that there is an effect of service quality and customer trust on customer loyalty through satisfaction as a mediating variable for BRILink Agent customers.